Service Innovation Strategy in Improving Service Quality at The Badan Pertanahan Nasional (BPN) Medan - Reika Dasha Mihwa; Yayuk Yuliana; Nurul Habibah; Putri Mita Azhari; Nur Elsa Harahap; Nur Aisyah Pratiwi (International Forum of Researchers and Lecturers, 2025)
This research aims to analyze service innovation strategies that can be applied at the National Land Agency (BPN) Medan in an effort to improve the quality of services to the public. In the digital era and with increasing public expectations, BPN Medan faces challenges in adapting and innovating to provide more efficient and effective services. The research method used is a combination of qualitative and quantitative approaches, with data collection through surveys, interviews, and document analysis. The results indicate that the implementation of information technology, enhancement of human resource competencies, and improvement of service processes are significant innovation strategies for improving service quality at BPN Medan. Additionally, this study also identifies factors that influence the successful implementation of service innovations, such as management support, community participation, and organizational culture. These findings are expected to provide useful recommendations for BPN Medan and other government agencies in their efforts to enhance the quality of public services in Indonesia.